HUBUNGAN REWARD & PUNISHMENT DAN PENGAWASAN KINERJA DENGAN KUALITAS DATA SENSUS HARIAN RAWAT INAP OLEH PERAWAT DI RS MARDI RAHAYU KUDUS - Rade Roro Yuke Rahma Febriani; Dharminto Dharminto; Yudhy Dharmawan (Jurnal Kesehatan Masyarakat (Undip), 2016)
Good data quality can be seen from the fulfillment functional dimensions data quality, namely: complete , accurate and timely .On preliminary study carried out at Mardi Rahayu Kudus Hospital achievement of completeness daily form in-patient census by 67,26% and achievement of accuracy daily form in-patient census by 60.34% .The purpose of this research was to describe the relationship reward & punishment and performance monitoring with data quality daily form in-patient census by nurse at the Mardi Rahayu Kudus Hospital.This research using descriptive analytic methods.The population research is nurses who have the main tasks and functions fill daily census in-patient care in 14 rooms. Samples fill some 11 nurses and 154 form daily census in-patient. The research results show the an index of reward & punishment on daily census in-patient (85%) , the index performance monitoring on daily census in-patient (84%), and data quality daily census in-patient (53.17%). Based on Spearman Rank Correlation statistical tests showed that the variables of reward & punishment and performance monitoring is not related to quality daily form in-patient census (sig. reward & punishment = 0,345 and sig. Performance monitoring= 0.872). Suggestions for nurses to fill daily form in-patient census and check before it’s collected. Medical records department  make SOP (Standard Operational Procedure) about fill daily form in-patient census. Head room to have regular monitoring of performance against the daily form in-patient census